S-Dual of Maxwell–Chern-Simons Theory - Adi Armoni (Physical Review Letters, 2023)
We discuss the dynamics of three-dimensional Maxwell theory coupled to a level-k Chern-Simons term. Motivated by S-duality in string theory, we argue that the theory admits an S-dual description. The S-dual theory contains a nongauge one-form field, previously proposed by Deser and Jackiw [Phys. Lett. 139B, 371 (1984).] and a level-k U(1) Chern-Simons term, Z_MCS=Z_DJ Z_CS. The couplings to external electric and magnetic currents and their string theory realizations are also discussed.